Lipid storage consumption and feeding ability of Calanus glacialis Jaschnov, 1955 males - Hatlebakk, Maja Karoline Viddal; Graeve, Martin; Boissonnot, Lauris; Søreide, Janne (Journal of Experimental Marine Biology and Ecology, 2019)
Calanus is one of the best studied genera of Arctic zooplankton, but still we know very little about the males since they are short-lived and mainly present in winter. Their short life-span compared to females is assumed to be a combination of high mating activity, no feeding and consequential depletion of lipid stores. In this study we tested 1) if the life span of male Calanus glacialis is limited by their lipid storage reserves and 2) if males are capable of feeding and utilize food if present. We ran two separate experiments from January to March; one on starvation and one on feeding. In the 39-days long starvation experiment we followed the lipid sac size of individually incubated males until their time of death. On average the total lipid (TL) content decreased by 2.6 to 4.5 μg day−1, but despite this males had substantial amounts of lipids left (131.4 μg, SD 44.0) when they died. This strongly suggests that the depletion of lipid reserves is not the main reason for males' short life span which in this study was measured to be up to 73 days. In the feeding experiment, we fed both C. glacialis males and females ad libitum with 13C labelled microalgae. Both males and females were capable of feeding and assimilate the diatom monoculture, but females responded faster to the sudden favourable food conditions, and produced more and larger fecal pellets than the males. Assimilation of 13C labelled 20:5(n-3), an essential polyunsaturated fatty acid (PUFA), from the diatom diet was traceable in both males and females on day 21, and then with a higher enrichment in females than males. Morphological investigations of the feeding appendages showed some differences between sexes, suggesting males to be more omnivorous than females. In conclusion, lipid storage depletion is not the cause of death for male C. glacialis, and males may even compensate for some of the mating energy costs by feeding. In future, we recommend further studies on the role of essential fatty acids (FA) for sperm formation and aging as determining ...